Differences in Learning Outcomes in Long Jump Squatting Through the Application of Demonstration Methods and Training Methods in Class XI Students of SMA Negeri 2 Central Maluku - Tehupelasura, Fakhrurrozie Z.; Fenanlampir, Albertus; Matitaputty, Johanna (International Journal of Education, Information Technology, and Others, 2024)
The research aims to determine and analyze the comparison of learning outcomes for the long jump squat style between the demonstration method and the training method for class XI students at SMA Negeri 2 Central Maluku. Data obtained through a survey using observation sheets and question sheets to assess the comparison of student learning outcomes. After the data is obtained, the data is then analyzed using the independent sample t test formula (Independent-Sampel-T-Test). Based on the results of data analysis and hypothesis testing, the results obtained are based on the mean and standard deviation values ​​that have been analyzedcountis 4.03 for ttableis 2.06 which means that tcount > ttable (4.03 > 2.06) while for ttable 2.79 with tcount4.03 points tcount > ttable (4.03 > 2.79) then the alternative hypothesis (Ha) accepted. In accordance with the hypothesis formula H0: there is no difference in the results of learning the squat style long jump between the demonstration method and the training method for class XI students at SMA Negeri 2 Central Maluku. Meanwhile for H1: there is a difference in the results of learning the long jump squat style between the demonstration method and the training method in class XI students at SMA Negeri 2 Central Maluku. So based on the results of the analysis above, it can be concluded that there is a significant difference in learning outcomes for the long jump squat style between the demonstration method and the training method for class XI students at SMA Negeri 2 Central Maluku.